2020
DOI: 10.3390/nu12123632
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Dietary Sodium Recommendations and Atherosclerotic Cardiovascular Disease Prevention through Culinary Medicine Education

Abstract: Sodium-reduction initiatives have been a cornerstone of preventing hypertension and broader atherosclerotic cardiovascular disease (ASCVD) since the early 1970s. For nearly 50 years, public health and clinical guidelines have concentrated on consumer education, behavioral change, and, to a lesser extent, food policy to help reduce sodium intake among Americans. While these efforts undoubtedly helped improve awareness, average sodium consumption remains at approximately 4200 mg/day in men and 3000 mg/day in wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…Our intervention presented engaging content, cooking demonstrations using a teaching kitchen, and recipes from the Mediterranean and DASH diets (high in fruits, vegetables, whole grains, and lean proteins, and low in red meats, sweets, saturated, and total fat) [ 63 ] and we showed an increase in adherence to a Mediterranean diet. There is very little research on the use of teaching kitchen or culinary skills as an intervention to reduce blood pressure [ 64 - 66 ]. In a study by Razavi et al [ 67 ], families living in New Orleans, Louisiana, were randomized to a hands-on teaching kitchen culinary education class or non–kitchen-based dietary counseling for 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Our intervention presented engaging content, cooking demonstrations using a teaching kitchen, and recipes from the Mediterranean and DASH diets (high in fruits, vegetables, whole grains, and lean proteins, and low in red meats, sweets, saturated, and total fat) [ 63 ] and we showed an increase in adherence to a Mediterranean diet. There is very little research on the use of teaching kitchen or culinary skills as an intervention to reduce blood pressure [ 64 - 66 ]. In a study by Razavi et al [ 67 ], families living in New Orleans, Louisiana, were randomized to a hands-on teaching kitchen culinary education class or non–kitchen-based dietary counseling for 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“… 17 For example, among patients with heart failure, those who have higher levels of FL have lower sodium consumption, improved control of their disease, and higher quality of life. 18 The qualitative study by Karin et al reported FL as a facilitator of adherence to dietary guidance and demonstrated a link to increased fruit and vegetable consumption in renal transplant recipients. 19 Additionally, lower FL is associated with food insecurity that increases the likelihood of progression from CKD to ESKD.…”
Section: Introductionmentioning
confidence: 99%
“…Food literacy is a scientific concept about control and prevention of food-borne diseases. Today, several communities are trying to change the human lifestyle by improvement of their food and nutrition literacy to avoid the diseases arising from foods ( Razavi et al, 2020 ; US Preventive Services Task Force et al, 2020 ). Owing to the high morbidity and mortality induced by NCDs in the world, increasing attention is paid to these illnesses and several interventions are programmed in this regard.…”
Section: Discussionmentioning
confidence: 99%